Independence of housewives through hydroponic urban farming as an effort to improve family economy - Mardiana, Ainun; Nurdiana; Supatminingsih, Tuti; Inanna; Hasan, Muhammad (Journal of Agrosociology and Sustainability, 2024)
Background: This research aims to delve into the potential of independence and increasing family economic income through hydroponic urban farming in the Women Farmers Group (KWT) of Anggrek, Bara-Baraya District, Makassar City, using a qualitative approach. The main focus of this research is to deeply understand how hydroponic urban farming affects the economy and independence of families, taking into account the experiences, perceptions, and social impacts of active participation in this activity. Methods: The research methodology used is a qualitative approach with in-depth interviews as the main data collection instrument. The research sample consists of 3 housewives and 1 government official who have been involved in hydroponic urban farming. The interview process was conducted in a structured manner, focusing on aspects of personal experience, changes in lifestyle, and the role of urban farming in improving family economics. This study is structured using qualitative analysis and further elaborated with descriptive writing methods. Findings: The research findings indicate that hydroponic urban farming has a significant positive impact on the independence and increasing economic income of families. Conclusion: Hydroponic urban farming significantly enhances women's economic self-reliance, offering policy insights for optimizing implementation and productivity. Novelty/Originality of this Study: This study explores the economic empowerment of urban housewives through hydroponic urban farming, specifically within the Anggrek’s KWT in Makassar City. This research uniquely addresses the dual impact of hydroponic farming on enhancing family income and ensuring food security, focusing on the often-overlooked demographic of housewives in urban settings.